(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2020)
This study deals with the demographic and socio-economic changes that took place in Lattakia Governorate during the last period and identifies the factors that have worked so strongly in this transformation during the previous period until it reached what it is now. These factors contributed effectively to the speed of this transformation. More clearly than the rest of the other governorates due to the strength of the influence of auxiliary factors, and the population of Lattakia are living the third phase of the stages of demographic transition, which is known as the slow growth stage, where birth rates and deaths are clearly and increases with the expected life expectancy, and This has happened only in limited governorates at the country level. يتناول هذا البحث التحولات الديموغرافية والاقتصادية الاجتماعية التي جرت في محافظة اللاذقية خلال الفترة الأخيرة , وتحديد العوامل التي عملت بشكل مؤثر في هذا التحول خلال الفترة السابقة إلى أن وصل إلى ما هو عليه الآن , حيث ساهمت تلك العوامل بشكل فعال على سرعة احداث هذا التحول الذي ظهر بشكل واضح أكثر من بقية المحافظات الأخرى نتيجة قوة تأثير العوامل المساعدة , وأصبح سكان محافظة اللاذقية يعيشون الطور الثالث من أطوار الانتقال الديموغرافي الذي يعرف بمرحلة النمو المتباطئ , حيث تنخفض معدلات الولادات والوفيات بشكل واضح ويرتفع معها الأمد المتوقع للحياة , وهذا لم يحدث إلا في محافظات محدودة على مستوى القطر .